2001
DOI: 10.1111/j.1939-165x.2001.tb00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Liver Cytology and Biopsy Diagnoses in Dogs and Cats: 56 Cases

Abstract: The results of liver cytology and corresponding biopsy specimens submitted to the Pathology Department at Angell Memorial Animal Hospital during 1998 were retrospectively reviewed to objectively assess the diagnostic value of liver cytology. A "corresponding" biopsy was defined as a biopsy specimen obtained within 1 day of the cytology specimen. Fifty-six cases were reviewed, including 25 from dogs and 31 from cats. Results were in complete agreement in 34 cases, in partial agreement in 11 cases, and in disagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 3 publications
3
57
0
1
Order By: Relevance
“…1 There are multiple examples in the domestic and human literature to indicate the superior diagnostic capability of biopsy over ultrasound-guided aspirate cytology. [2][3][4] There are also many examples of how endoscopy, being less invasive, is less traumatic and less painful than traditional surgical approaches. In human medicine, faster recovery, reduced hospital stay, and decreased pain scores have been attributed to endoscopic procedures.…”
Section: The Endoscopic Solutionmentioning
confidence: 98%
“…1 There are multiple examples in the domestic and human literature to indicate the superior diagnostic capability of biopsy over ultrasound-guided aspirate cytology. [2][3][4] There are also many examples of how endoscopy, being less invasive, is less traumatic and less painful than traditional surgical approaches. In human medicine, faster recovery, reduced hospital stay, and decreased pain scores have been attributed to endoscopic procedures.…”
Section: The Endoscopic Solutionmentioning
confidence: 98%
“…Comparisons between liver biopsy and fine-needle aspiration in dogs and cats have indicated that aspiration cytology was only 30-61% diagnostic compared with histopathology. 29,34 Compared with surgical wedge samples, large-gauge needle-biopsies were diagnostic in only 48% of cases and should be interpreted with caution. 3 Although the improved diagnostic value of surgical biopsy over needlebiopsy and fine-needle aspiration has been demonstrated, the increased surgical intervention is a disadvantage that has been largely overcome since the development of minimally invasive endoscopic techniques.…”
Section: Introductionmentioning
confidence: 94%
“…Aspiration cytology was found to be of diagnostic value in only 30-61% of cases compared with histology in studies comparing liver biopsy and fine-needle aspiration in dogs and cats (Roth 2001;Wang et al 2004). In comparison to surgical wedge samples, large-gauge needle-biopsies were of diagnostic value in only 48% of cases and they should be interpreted with a certain degree of caution (Cole et al 2002).…”
Section: Variablesmentioning
confidence: 99%